The State papers domestic for the years 1655-1656 of the Interregnum - Cromwell, Oliver, 1599-1658 (Complete state papers domestic. Series two. 1625-1702. ;, 1655)
Letters and miscellaneous government papers, including Orders of the Council of State, petitions, etc.; Admiralty Committee and Navy Commissioners' papers; Navy bonds for the sick and wounded, etc.; Admiralty Committee warrants; Navy petitions, etc.; and Customs, Excise, and Exchequer accounts.